A Pt–Ir nanocube amplified lateral flow immunoassay for dehydroepiandrosterone. Issue 8 (12th March 2021) - Yang, Huiyi; He, Qiyi; Pan, Junkang; Shen, Ding; Xiao, Huanxin; Cui, Xiping; Zhao, Suqing
Abstract : A Pt–Ir nanocube amplified lateral flow immunoassay for dehydroepiandrosterone determination was demonstrated. Abstract : The traditional gold-nanoparticle-based lateral flow immunoassay (LFIA) cannot satisfy the requirements for the sensitive detection of dehydroepiandrosterone (DHEA) in human urine. To enhance the sensitivity of the LFIA, platinum–iridium nanocubes (Pt–Ir NCs) with high catalytic efficiency and stability were synthesized and labelled with polyclonal antibody (pAb) to form a pAb–Pt–Ir probe. For the detection of DHEA, a novel LFIA with Pt–Ir NCs as an optical label and an enhanced LFIA in which the peroxidase-like activity of the Pt–Ir NCs was triggered by the introduction of the chromogenic substrate 3-amino-9-ethyl-carbazole (AEC) were developed and compared with a LFIA with platinum nanocubes (PtNCs) as an optical label. The visual limit of detection was 0.5 ng mL −1 for Pt–Ir-LFIA and 0.05 ng mL −1 for AEC-enhanced Pt–Ir-LFIA, in comparison to 100 ng mL −1 for PtNCs-LFIA and 50 ng mL −1 for AEC-enhanced PtNCs-LFIA. The average recoveries from spiked urine samples ranged from 90.8% to 110.4%, with a coefficient of variation below 12.6%, suggesting the accuracy and reliability of our developed immunoassay. Achieving excellent sensitivity, specificity, and reproducibility, Pt–Ir-LFIA provided a promising platform for monitoring DHEA.